Compressive strength of masonry constructed with high strength concrete blocks - Fortes, E. S.; Parsekian, G. A.; Camacho, J. S. [UNESP]; Fonseca, F. S. (IBRACON - Instituto Brasileiro do Concreto, 2017)
Although the use of high strength concrete blocks for the construction of tall buildings is becoming common in Brazil, their mechanical properties and behavior are not fully understood. The literature shows a gap in experimental studies with the use of high strength concrete blocks, i.e., those with compressive strength greater than 16 MPa. The work presented herein was conducted in order to study the behavior of high strength structural masonry. Therefore, the compressive strength and modulus of elasticity of concrete block walls tested under axial load were assessed. The specimens included grouted and ungrouted walls and walls with a mid-height bond beam; ungrouted walls were constructed with face-shell and full mortar bedding. The walls were built and tested in the laboratory of CESP and in the Structures Laboratory of the UNESP Civil Engineering Department in Ilha Solteira (NEPAE). Concrete blocks with nominal compressive strength of 16 (B1), 24 (B2) and 30 (B3) MPa were used. Ungrouted masonry walls had a height of 220 cm and a width of 120 cm while grouted masonry walls had a height of 220 cm and a width of 80 cm. Traditional Portland cement, sand and lime mortar was used. The testing program included 36 blocks, 18 prisms, 9 ungrouted walls (6 with face-shell mortar bedding and 3 with full mortar bedding), 9 grouted masonry walls, and 12 ungrouted walls with a bond beam at mid-height. The experimental results were used to determine the compressive strength ratio between masonry units, prisms and masonry walls. The analyses included assessing the cracking pattern, the mode of failure and the stress-strain curve of the masonry walls. Tests results indicate that the prism-to-unit strength ratio varies according to the block strength; that face-shell mortar bedding is suitable for high strength concrete masonry; and that 20% resistance decrease for face-shell mortar bedding when compared with full mortar bedding is a conservative consideration. The results also show that using a bond beam at the mid-height of the wall does not lead to a compressive strength decreased but it changes the failure mode and the shape of the stress-strain curve. In addition, the results show that estimating E = 800 fp is conservative for ungrouted masonry walls but reasonably accurate for grouted masonry walls and that there is no reason to limit the value of E to a maximum value of 16 GPa. Furthermore, the results show that, for design purposes, a wall-to-prism strength ratio value of 0.7 may be used for high strength concrete masonry.
Keywords: structural masonry; concrete block; high strenght; compressive strenght; high-rise buildings.